Electronic and photovoltaic properties of Al/p-Si/copper phthalocyanine photodiode junction barrier - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
Al/p-Si/copper phthalocyanine photovoltaic device has been fabricated and characterised by current-voltage and capacitance-voltage measurements. Electrical properties of the device were determined by current-voltage characterizations under dark and illumination conditions. The density distribution of the interface states of the photodiode was found to vary from 8.88 x 10(12) eV(-1)cm(-2) in E-ss-O. 54 eV to 4.51 X 10(12) eV(-1) cm(-2) in E-ss-0.61 eV. The device shows a photovoltaic behaviour with a maximum open circuit voltage Voc of 0.16V and short-circuits current I-sc of 0.45 mu A under 3500 lux light intensity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: photodiode; organic semiconductor; phthalocyanine